Intraseasonal Variations of Nonmigrating Tides Observed Near the Mesopause. Issue 11 (28th November 2018) - Liu, Guiping; Janches, Diego; Lieberman, Ruth S.
Abstract: Nonmigrating tides excited in the tropical troposphere by latent heat release from deep convection are known to be responsible for introducing the longitudinal structures in the upper atmosphere and the ionosphere. This study presents for the first time an extensive analysis of the prominent wave‐3 and wave‐4 longitudinal structures using nearly 14 years of temperature observations by the Microwave Limb Sounder instrument operated on the Aura satellite from 2004 to 2017. The observations reveal significant intraseasonal (~30–60 days) periodic variations in the amplitudes of these wave structures at ~97‐km altitude near the mesopause. Some large wave amplitudes accompany strong activity of the Madden‐Julian Oscillation. Rainfall data from the Tropical Rainfall Measuring Mission are used as a proxy of latent heating to investigate the source of these variations. Intraseasonal signatures in the wave structures are observed to coincide with the rainfall variations, indicating that the tropospheric 30‐ to 60‐day oscillation is an important driver of the same periodic changes in the upper atmosphere. Given that not all intraseasonal oscillations in the lower atmosphere have corresponding signatures in the longitudinal wave structures, the atmospheric conditions and other influences are important. This study provides evidence on the connection between intraseasonal variations of tides in the upper atmosphere and the changes in the forcing by latent heat release in the troposphere. Key Points: We perform a study of intraseasonal variability of nonmigrating tides at ~97‐km altitude using the MLS multiyear temperature observations Approximately 30‐ to 60‐day periodicities are observed in the amplitudes of wave‐3 and wave‐4 longitudinal structures Intraseasonal variations of the wave‐3 and wave‐4 structures are found to coincide with the corresponding periodic signatures in rainfall